Trauma representation in A Space for the Unbound video game - Alfaini, Sana; Adji, Muhamad; Hidayatullah, Mochamad Irfan (Universitas Muhammadiyah Malang, 2026)
This study examines how trauma is represented through the integration of narrative and gameplay in A Space for the Unbound. While video games increasingly function as complex storytelling media, the mechanisms by which interactive systems convey psychological trauma remain underexplored. The aim of this research is to identify and explain strategies for trauma representation through spatial disruption, restrictions on player agency, memory fragmentation, and temporal structures characterized by repetition and belatedness. Employing a qualitative multimodal approach, the study treats the video game as an interactive text, analyzing selected gameplay segments through purposive sampling. Data consisting of gameplay recordings and screenshots were examined using ludonarrative analysis, supported by Cathy Caruth's trauma theory and narratology. The results reveal four main findings regarding trauma representation: (1) spatial disorientation within the environment, (2) restrictions on player control, (3) memory fragmentation in a liminal analeptic space, and (4) patterns of repetition and delayed trauma. The study concludes that trauma in narrative-driven video games operates as an experiential structure produced through player interaction, where storytelling, mechanics, and spatial design collectively construct trauma as both a narrative theme and an interactive process. Studi ini meneliti bagaimana trauma direpresentasikan melalui integrasi narasi dan gameplay dalam A Space for the Unbound. Meskipun video game semakin berfungsi sebagai media bercerita yang kompleks, mekanisme bagaimana sistem interaktif menyampaikan trauma psikologis masih kurang dieksplorasi. Tujuan penelitian ini adalah untuk mengidentifikasi dan menjelaskan strategi representasi trauma melalui gangguan spasial, pembatasan pada agensi pemain, fragmentasi memori, dan struktur temporal yang ditandai dengan pengulangan dan keterlambatan. Dengan menggunakan pendekatan multimodal kualitatif, studi ini memperlakukan video game sebagai teks interaktif, menganalisis segmen gameplay terpilih melalui pengambilan sampel bertujuan. Data yang terdiri dari rekaman gameplay dan tangkapan layar diperiksa menggunakan analisis ludonaratif, yang didukung oleh teori trauma dan naratologi Cathy Caruth. Hasilnya mengungkapkan empat temuan utama mengenai representasi trauma: (1) disorientasi spasial dalam lingkungan, (2) pembatasan pada kontrol pemain, (3) fragmentasi memori dalam ruang analeptik liminal, dan (4) pola pengulangan dan trauma tertunda. Studi ini menyimpulkan bahwa trauma dalam gim video berbasis narasi beroperasi sebagai struktur pengalaman yang dihasilkan melalui interaksi pemain, di mana penceritaan, mekanisme, dan desain spasial secara kolektif membangun trauma sebagai tema naratif dan proses interaktif.